The Utilization of Comic as Learning Media to Fulfill Student's Learning Needs - Dian Wicaksono; Wanda Nugroho Yanuarto (UM Purwokerto Press, 2025)
According to national educational report card, SDN Semaya achieved score 63.1 which classified as moderate in terms of learning quality matters. The quality of learning has a root problem in the form of